Circulating CD24hiCD38hi regulatory B cells correlate inversely with the ThEM17 cell frequency in granulomatosis with polyangiitis patients. (10th January 2019) - von Borstel, Anouk; Lintermans, Lucas L; Heeringa, Peter; Rutgers, Abraham; Stegeman, Coen A; Sanders, Jan Stephan; Abdulahad, Wayel H
Abstract: Objectives: To investigate whether there is a direct relation between expanded proportions of Th17 effector memory (ThEM 17) cells and regulatory B cells (Bregs) in peripheral blood of granulomatosis with polyangiitis (GPA) patients. Methods: Frequencies of Bregs and ThEM 17 cells, as well as ThEM 1 cells, were determined by flow cytometry in blood samples from 42 GPA patients in remission and 18 matched healthy controls (HCs). The Breg frequency was defined as CD24 hi CD38 hi CD19 + cells. ThEM 17 cells were defined as CCR6 + CXCR3 - CCR4 + cells and ThEM 1 cells as CCR6 - CXCR3 + CCR4 - cells within the CD3 + CD4 + CD45RO + CCR7 - population. In addition, CD3 + CD4 + Th cells from 9 GPA patients were co-cultured in vitro with either total B cells or a Breg-depleted B cell fraction. Cultured cells were stimulated with Staphylococcus Enterotoxin B (SEB) and CpG-oligodeoxynucleotides (CpG-ODN). Th17- (IL-17 + ) and Th1 cell (IFNγ + ) frequencies were determined at baseline and day 5 upon restimulation with phorbol myristate acetate (PMA) and Ca-I. Results: A decreased Breg frequency was found in treated GPA patients, whereas an increased ThEM 17 cell frequency was observed in treated and untreated GPA patients compared with HCs. Additionally, a decreased ThEM 1 cell frequency was seen in untreated GPA patients compared with HCs. In untreated GPA patients circulating Breg frequencies correlated negatively with ThEM 17 cells ( r = −0.533; P = 0.007) and positively with ThEM 1 cells ( r = −0.473; P = 0.015). The co-culture experiments revealed a significant increase in the frequency of IL-17 + Th cells in Breg-depleted samples (median: 3%; range: 1–7.5%) compared with Breg-undepleted samples ( P = 0.002; undepleted samples median: 2.1%; range: 0.9–6.4%), whereas no difference in the frequency of IFNγ + Th cells in Breg-depleted cultures was observed (undepleted median: 11.8%; range: 2.8–21% vs Breg-depleted median: 12.2%; range: 2.6–17.6%). Conclusion: Bregs modulate ThEM 17 responses in GPA patients. Future studies should elaborate on clinical and therapeutical implications of the Breg-Th17 interaction in GPA patients.